MENGEMBANGKAN POTENSI GURU YANG PROFESIONAL DALAM PROSES BELAJAR MENGAJAR - Hayani Wulandari; Isa Nurhaliza (STKIP Subang, 2023)
Potential is an individual ability that must continue to be developed especially by teachers (in particular), because the potential of teachers who continue to develop maturely in carrying out the teaching and learning process will affect good results. Likewise, if the lack of potential possessed by a teacher will have an impact on the results of the teaching and learning process that are not good or inadequate. Therefore, the purpose of this article is to find out how to develop professional teacher potential in the teaching and learning process to achieve the right learning goals. This journal article is a type of qualitative descriptive study of literature studies accompanied by library research that seeks to explain how to develop teacher potential in the teaching and learning process. In this literature review review using various written sources such as articles, journals, and documents related to the study in this research. By reading and analyzing literacy studies, it is hoped that the potential of professional teachers can be increased in the teaching and learning process.